(untitled) (Gaceta Técnica, 2023)
This Correction is to clarify and replace the differences in the article in Gaceta Técnica, Volume 23, Number 2, July-December, p. 107-122 between what was published and what the author subsequently sends as clarifications in order to proceed to publication. The Editorial Committee is not responsible for these differences